2020
DOI: 10.1097/scs.0000000000006940
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Changes Following Different Orthognathic Surgeries, Evaluated by Cone Beam Computed Tomography: A Systematic Review and Meta-analysis

Abstract: Purpose: This study sought to assess the upper airway changes following different orthognathic surgeries using cone-beam computed tomography. Methods: An electronic search of the literature was conducted in major electronic databases including Medline (PubMed), Web of Science, Scopus, and Open Grey for articles published up to January 20, 2018. Human studies that evaluated the changes in the volume and minimum cross-sectional area of the upper airway or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Only two systematic reviews on airway volumetric measurements obtained from CBCT have been published previously, with one demonstrating less reduction of the volume after bimaxillary surgery than mandibular setback only in patients with a class III malocclusion, 11 and the other showing a significant volume increase after mandibular advancement in patients with mandibular deficiency. 12 In comparison, the present study is novel in providing a comprehensive overview of the volumetric changes of both the total airway and the three airway segments, and including the different types of orthognathic surgery reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two systematic reviews on airway volumetric measurements obtained from CBCT have been published previously, with one demonstrating less reduction of the volume after bimaxillary surgery than mandibular setback only in patients with a class III malocclusion, 11 and the other showing a significant volume increase after mandibular advancement in patients with mandibular deficiency. 12 In comparison, the present study is novel in providing a comprehensive overview of the volumetric changes of both the total airway and the three airway segments, and including the different types of orthognathic surgery reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…He et al 11 investigated only patients with class III malocclusion and showed less reduction in the airway volume after bimaxillary surgery than after mandibular setback surgery only. More recently, Shokri et al 12 focused on mandibular advancement and demonstrated a significant volumetric increase in the upper airway. However, a comprehensive overview of the current literature on the effects of different types of orthognathic surgery on volumetric changes to the total airway and to the airway segments is still lacking.…”
mentioning
confidence: 99%
“…En la actualidad los cirujanos disponemos de tres herramientas fundamentales para el diagnóstico topográfico de la AOS: la exploración física en consulta, la exploración bajo sueño inducido (DISE o somnoscopia) y la tomografía computarizada (TC), en especial la de haz cónico (tecnología ConeBeam). Esta última técnica permite una precisa evaluación anatómica de la VAS y está validada para establecer parámetros volumétricos y áreas seccionales en el espacio aéreo posterior, que son esenciales para planificar la cirugía esquelética [5], con la ayuda de los diferentes programas informáticos de los que disponemos. Igualmente, estas mediciones nos permiten hacer estudios comparativos pre y postoperatorios con el fin de establecer la mejora objetiva de los parámetros anatómicos (Figura 1).…”
Section: Introductionunclassified
“…Pharyngeal dimensions in sagittal and vertical facial patterns are important aspects for the diagnosis and planning of orthodontic treatment [8]. This morphological analysis can be performed using two-or three-dimensional images from cephalometric radiograph, cone-beam computed tomography (CBCT), and magnetic resonance imaging (MRI) [2,5,11,12]. The association between airway changes and facial growth patterns has not been established, nor have sex differences in determining factors for orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%